(untitled) (INPAC: Innovative Public Accounting and Compliance, 2026)
This study examines the influence of local government budgeting on the quality of public services in Indonesia within the framework of fiscal decentralization. Using a qualitative descriptive phenomenological approach, this research analyzes the dynamics of planning, allocation, and realization of Regional Revenue and Expenditure Budgets (APBD) in three districts with differing levels of fiscal capacity over the period 2019–2025. Data were collected through in-depth interviews, participatory observation, focus group discussions, and analysis of APBD documents and the Community Satisfaction Index (IKM). The findings indicate that APBD structures remain heavily dominated by central government transfers, resulting in high fiscal dependency, with personnel and operational expenditure proportions exceeding ideal thresholds while capital expenditure for public services remains relatively low. Budget allocation patterns are not fully aligned with actual community needs, particularly in regions with low locally-generated revenue, thereby creating disparities in public service quality across regions. Low budget absorption efficiency, limited transparency, and the dominance of political interests further undermine public service performance. These findings underscore that improvements in public service quality depend not only on fiscal capacity but also on managerial effectiveness and performance-based, participatory, and outcome-oriented budgeting governance.